Endothelial mediators of 17ß-estradiol-induced coronary vasodilation in the isolated rat heart - Santos,R.L. (2004)
The present study was designed to determine relaxation in response to 17ß-estradiol by isolated perfused hearts from intact normotensive male and female rats as well as the contribution of endothelium and its relaxing factors to this action. Baseline coronary perfusion pressure was determined and the vasoactive effects of 17ß-estradiol (10 µM) were assessed by in bolus administration before and after endothelium denudation by infusion of 0.25 µM sodium deoxycholate or perfusion with 100 µM L-NAME, 2.8 µM indomethacin, 0.75 µM clotrimazole, 100 µM L-NAME plus 2.8 µM indomethacin, and 100 µM L-NAME plus 0.75 µM clotrimazole. Baseline coronary perfusion pressure differed significantly between males (84 ± 2 mmHg, N = 61) and females (102 ± 2 mmHg, N = 61). Bolus injection of 10 µM 17ß-estradiol elicited a transient relaxing response in all groups, which was greater in coronary beds from females. For both sexes, the relaxing response to 17ß-estradiol was at least in part endothelium-dependent. In the presence of the nitric oxide synthase inhibitor L-NAME, the relaxing response to 17ß-estradiol was reduced only in females. Nevertheless, in the presence of indomethacin, a cyclooxygenase inhibitor, or clotrimazole, a cytochrome P450 inhibitor, the 17ß-estradiol response was significantly reduced in both groups. In addition, combined treatment with L-NAME plus indomethacin or L-NAME plus clotrimazole also reduced the 17ß-estradiol response in both groups. These results indicate the importance of prostacyclin and endothelium-derived hyperpolarizing factor in the relaxing response to 17ß-estradiol. 17ß-estradiol-induced relaxation may play an important role in the regulation of coronary tone and this may be one of the reasons why estrogen replacement therapy reduces the risk of coronary heart disease in postmenopausal women.